Influence of freezing down to 77.15 K on structure and antioxidant power of some proteins - Rozanova, S.L.; Narozhnyi, S.V.; Nardid, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The purpose of the present work was to investigate influence of different freeze-thawing protocols on structure and antioxidant properties of isolated proteins. In our experiments we have studied human serum albumin, human hemoglobin and cytochrome C derived from equine heart frozen down to 77.15 K with 1–2 deg/min and 300 deg/min rate with following thawing on a water bath at 293.15 K. Native proteins were assumed as a control. Influence of freeze-thawing protocols on protein structure was investigated using spectrophotometric and fluorescent assays. Antioxidant activities of isolated proteins were estimated by their ability to reduce ABTS+ radical. It has been established that unfolding derived from freeze-thawing exposure leads to protein antioxidant activity increasing while decreasing of such an activity may be connected with macromolecule aggregation. Character of freeze-thawing influence on antioxidant activity of proteins depends on molecule structure peculiarities and freezing protocols.